PERLINDUNGAN HUKUM BAGI PENCIPTA LAGU ATAS LAGU CIPTAANNYA YANG DIPAKAI ORANG LAIN TANPA IZIN - Marbun, Kolosse Bestanta; Purba, Jeshanta Elshadai; Agustina, Yanti (Collegium Studiosum Journal, 2023)
Creating a work of music that has economic value is not something that everyone can do, because creation requires creativity, effort, and costs, therefore the rights of the person who creates a work of music must be protected and respected. This protection has been proven by the existence of Act Number 28 of 2014 concerning Copyright, the enactment of this law is due to the many copyright violations in Indonesia where one of these copyright violations will be discussed in this journal. This journal uses research methods of juridical analysis and qualitative data analysis. Protection of the creator's rights has been formulated in Law Number 28 of 2014 concerning Copyright, where the creator and the right holder are the authorities and have full control over their creation, therefore parties who wish to use the work belonging to the creator must obtain prior permission from the creator.